Effect of lanthanum on thermal and mechanical properties of modified polyvinyl chloride film. (15th February 2023) - Chen, Yan; Lu, Yi-Heng; Lu, Yu-Wei
Abstract: Polyvinyl chloride (PVC) hybrid film containing cerium, tin and folic acid modified nano titanium dioxide is a new functional material with good compatibility, light resistance and heat resistance. In this work, the PVC hybrid film was prepared by replacing cerium with lanthanum. The hybrid film was characterized by thermogravimetric infrared spectroscopy, dynamic mechanical analysis, atomic force microscopy, x-ray photoelectron spectroscopy, scanning electron microscopy, tensile strength and thermal aging. The results show that the initial thermal stability of the hybrid film containing lanthanum is slightly higher than that of the control sample (conversion α < 1.9%). For the same gaseous component plasticizer, the peak intensity of the ester based infrared characteristic group is higher than that of the hybrid film containing lanthanum, indicating that the intermolecular force between lanthanum and plasticizer is greater than that of cerium. In the range of 350 °C–575 °C and the wave number range of 2850–3100 cm −1, the peak height of the lanthanum containing film is significantly higher than that of the control sample, which may be due to the difference of the outer layer electrons. The peak intensity of O and C atoms on the surface of the hybrid film containing lanthanum is significantly lower than that of the control sample, indicating that the surface relative concentration of lanthanum atoms is lower than that of cerium atoms. The surface roughness RMS of the hybrid film containing lanthanum is significantly lower than that of the organic tin film, which is the result of the attraction between folic acid modified TiO2, lanthanum and tin and the carbon chlorine bond in PVC. It has the function of a potential ultrafiltration membrane. In addition, the hybrid film containing 1phr lanthanum shows good energy storage modulus and low temperature resistance. The prepared hybrid film shows the characteristics of a potential multi-functional material.